The effect of dismissals on work-rate in English FA Premier League soccer - O'Donoghue, P.; Robinson, G. (International Journal of Performance Analysis in Sport, 2016)
The current paper studies the effect of dismissals on work-rate in English FA Premier League soccer. The study included 28 matches where a team had a player dismissed while they were winning by a single goal or the score was level. Two types of match were compared; matches where the team reduced to 10 players maintained the drawing or winning score-line until the end of the match and matches where they failed to do so. Similar reductions in work-rate variables were observed for teams reduced to 10 players and for their opponents after the dismissal irrespective of the outcome of the match. A significant interaction effect of team (the team reduced to 10 players v the team that played with 11 players throughout the match), match period (before v after the dismissal) and type of match was found on the percentage of time spent in the defending and attacking thirds (p